ESMO management and treatment adapted recommendations in the COVID-19 era: colorectal cancer - Vecchione, Loredana (ESMO Open, 2020)
COVID-19 pandemic challenges health system capacities in many countries. National healthcare services have to manage unexpected shortage of healthcare resources that have to be reallocated according to the principles of fair and ethical prioritisation, in order to maintain the highest levels of care to all patients, ensure the safety of patients and healthcare workers and save as many lives as possible. Beyond that, cancer care services have to pursue restructuring, following the same evidence-based dispositions. In this article, we propose guidance to the management of colorectal cancer during the pandemic, prioritised according to a three-tiered framework, based on expert clinical judgement and magnitude of benefit expected from specific interventions. Since the availability of resources for diagnostic procedures, surgery and postoperative care, systemic therapy and radiotherapy may differ, authors did separate prioritisation analyses. The impact of postponing or abrogating cancer interventions on outcomes according to a high, medium or low priority scale, is outlined and discussed. The implementation of healthcare services using telemedicine is explored: it reveals itself as functional and effective for limiting patients’ need to travel to centres and thereby has the potential to reduce diffusion of severe acute respiratory syndrome coronavirus 2. Colorectal cancer demands a considerable amount of medical resources. Therefore, the redefinition of its diagnostic and therapeutic algorithms with a rigorous method is crucial in order to ensure the highest quality of continuum of care in the broader context of the pandemic and the challenged healthcare systems.